Increasing Interest and Learning Outcomes in Sociology with the Problem Based Learning Model (PBL) Learning Model for Class X IPS Students at SMA Negeri 1 Kuala Behe - Supardi, Supardi; Bahari, Yohanes; Suratman, Dede (Universitas Tanjungpura, 2024)
The purpose of this study was to observe the problem-based learning model in an effort to improve students' interest and learning outcomes. This study used the Classroom Action Research (CAR) approach. In this study, the sociology teacher acted as the actor and the researcher as a collaborative partner as an observer. The learning process was conducted in 2 cycles, with 4 meetings in each cycle, consisting of action planning, action implementation, observation, and reflection. The data collection tools in this study were observation to observe students' learning interest, observation of teacher activities, tests to determine students' learning outcomes, and documentation. The results of this study showed that the sociology teacher's teaching using the problem-based learning model in cycle I and cycle II improved, as well as students' learning interest, which showed improvement in both cycles. Based on the research data, it was found that students' learning outcomes also improved from the pre-test and post-test results, with improvements in learning mastery for each cycle.